Revolutionary barium titanate-BlueP/TMDCs SPR sensor: Ultra-sensitive detection of urine glucose levels - Momen Sahriar Shoshi; Md Abu Huraiya; Vinoth Raj R; Abror Jawad; Chang Yi Kong; Hitoshi Tabata; Sankar Ganesh Ramaraj; S.M. Abdur Razzak (Talanta Open)
This study represents a new design for an empathetic surface plasmon resonance (SPR) sensor that utilizes BlueP/TMDCs and BaTiO3 (barium titanate) and employs the angular interrogation technique to measure the glucose concentration level in urine samples. This design optimization involved extensive numerical analysis through the use of the Transfer Matrix Method (TMM) at a visible wavelength of λ=633 nm to enhance sensitivity, full width half maximum (FWHM), detection accuracy (DA), and quality factor (QF). Additionally, Finite Element Method (FEM) analysis was used to ensure the accuracy of the findings achieved through Transfer Matrix Method (TMM). The suggested biosensor configuration involves five layers: a BK-7 glass prism, 56 nm Ag layer, 11 nm BaTiO3 layer, BlueP/TMDCs with thickness of 0.68 nm, and a sensing medium (urine sample). Unlike earlier designs relying on conventional 2D materials or single dielectric layers, the proposed hybrid structure not only enhances light-matter interaction and optimizes electromagnetic field distribution but also outperforms other hybrid sensors by achieving superior sensitivity, detection accuracy, and quality factor. Through the use of novel combination of BlueP/TMDCs and BaTiO₃ in this hybrid sensor, the biosensor achieved significantly improved performance, with enhanced sensitivity of 435 deg/RIU at a concentration of glucose 10 g/dL, QF of 86.29442 RIU−1 as well as DA of 0.190114 deg−1 spanning a refractive index (RI) from 1.335 to 1.347.